The Image of Neighbouring Country and Selfidentification Issues in “Make Your Own Paradise” by M. Shchygel - Olesia Kalyniushko (Pitannâ Lìteraturoznavstva)
An article analyses M. Shchygel’s travelogue “Make Your Own Paradise” from the imagological viewpoint. Czech Republic occupies a special place on the sympathy scale among the Polish, even though, geographically it belongs to Eastern Europe and Czechs in return are much more restrained about the Polish people. Despite the narrator’s genuine delight about the Czech Republic, he unwraps the story, depicting Czechs critically, and subconsciously trying to rehabilitate the people of Poland uncertain in their European identity. It is important for the author to define both pros and cons of the Czech national identity, comparing them with the specificity of Polish nature, and thus demonstrating the ethnocentrism of his love for the Czech Republic. Traveller’s discovery of the country, which typically takes highest levels of the Polish sympathy scale, through the prism of the national values demonstrates his inner need (as the representative of “Not-Enough-European” country) to enhance its status having compared it with the country, which is higher appreciated by Poles than any of Western European countries. Another reason of character’s attention to the Czech Republic consists in his national guilty conscience that he shares with his nation, recognizing himself responsible for actions of his compatriots who supported the Soviet Union in August in 1968 and invaded Czechoslovakia as the part of five armies of the Warsaw Pact. Hence, getting to know the Czech Republic traveller of M. Shchygel’s travelogue “Make Your Own Paradise” states his Polish identity by means of comparing and analysing the specificity of Polish and Czech national characters. He calls himself a Czechophil, although he sets aside idealization of the Czech Republic in order to exonerate his people.